しらせ搭載全天カメラ及び雲底高度計によって観測された雲量の特徴 - 久慈, 誠; 萩原, 美沙子; 堀, 雅裕; 武田, 真憲; 平沢, 尚彦; 塩原, 匡貴; Makoto, Kuji; Misako, Hagiwara; Masahiro, Hori; Masanori, Takeda; Naohiko, Hirasawa; Masataka, Shiobara (2017)
第8回極域科学シンポジウム/個別セッション：[OM] 極域気水圏 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OM] Polar Meteorology and Glaciology Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object